Effective sequential combined therapy with carboplatin and a CDC7 inhibitor in ovarian cancer - Li, Junping; Hu, Hong; He, Jinping; Hu, Yuling; Liu, Manting; Cao, Bihui; Chen, Dongni; Ye, Xiaodie; Zhang, Jian; Zhang, Zhiru; Long, Wen; Lian, Hui; et al. (Translational oncology, 2024)
•A CDC7 inhibitor XL413 effectively enhanced the chemotherapeutic effect of carboplatin.•Mechanistically, the CDC7 inhibitor XL413 increases the accumulation of chemotherapy-induced DNA damage by inhibiting homologous recombination repair activity and delaying the recovery of DNA double-strand breaks.•XL413 reduced relapses after treatment with carboplatin in vitro and in vivo. The enhancement of DNA damage repair is one of the important mechanisms of platinum resistance. Protein cell division cycle 7 (CDC7) is a conserved serine/threonine kinase that plays important roles in the initiation of DNA replication and is associated with chemotherapy resistance in ovarian cancer. However, whether the CDC7 inhibitor XL413 has antitumor activity against ovarian cancer and its relationship with chemosensitivity remain poorly elucidated. We evaluated the antitumor effects of carboplatin combined with XL413 for ovarian cancer in vitro and in vivo. Cell viability inhibition, colony formation and apoptosis were assessed. The molecules related to DNA repair and damage were investigated. The antitumor effects of carboplatin combined with XL413 were also evaluated in SKOV-3 and OVCAR-3 xenografts in subcutaneous and intraperitoneal tumor models. Sequential administration of XL413 after carboplatin (CBP) prevented cellular proliferation and promoted apoptosis in ovarian cancer (OC) cells. Compared with the CBP group, the expression level of RAD51 was significantly decreased and the expression level of γH2AX was significantly increased in the sequential combination treatment group. The equential combination treatment could significantly inhibit tumor growth in the subcutaneous and intraperitoneal tumor models, with the expression of RAD51 and Ki67 significantly decreased and the expression of γH2AX increased. Sequential administration of CDC7 inhibitor XL413 after carboplatin can enhance the chemotherapeutic effect of carboplatin on ovarian cancer cells. The mechanism may be that CDC7 inhibitor XL413 increases the accumulation of chemotherapy-induced DNA damage by inhibiting homologous recombination repair activity.